Role of pattern recognition receptors and microbiota-derived ligands in obesity - Rolland, Alice; Douard, Véronique; Lapaque, Nicolas (Frontiers in Microbiomes, 2024)
Obesity is associated with activation of low-grade inflammation in tissues metabolically relevant for the regulation glucose homeostasis. The gut microbiota has been extensively linked to the inflammatory responses observed during obesity emphasizing the interconnection between host immunity and metabolism during obesity. Gut microbiota together with alteration of the gut barrier functions provide a myriad of circulating ligands for the pattern recognition receptors (PRRs) expressed in innate immune cells and nonimmune cells. PRR-dependent signalling drives the expression of a wide range of genes beyond the inflammatory response depending on the specific functions of the targeted cells and on the physiological context. PRRs activation can have opposite effects on host metabolic inflammation. Nucleotide-binding oligomerization domain 1 (NOD1) or NOD-like Receptor pyrin domain containing 3 (NLRP3) activation promote metabolic inflammation and insulin resistance while NOD2 activation improves insulin sensitivity and glucose homeostasis during obesity. Toll-like receptors (TLRs) 2, 4 and 5 also display specific effects on metabolic tissues. TLR5 deficient mice are prone to obesity and inflammation in response to high fat diet, while injection of TLR5 ligand, flagellin, has a protective effect toward diet-induced obesity. To the opposite TLR2 and 4 activations are associated with deleterious metabolic outcome during obesity. TLR4 activation enhances metabolic inflammation and insulin resistance and TLR2 via its activation by molecules derived from the gut microbiota favours the onset of obesity. It is now clear that activation of PRRs by bacterial derived molecules plays a key role in the host metabolic regulation. PRRs are expressed in various cell types complicating the understanding of the mechanisms underlying the relationship between PRRs activation/silencing and metabolic inflammation in obesity context. This review presents an overview of the current understanding of the interrelationship between the gut microbiota and PRRs, with a focus on its consequences for obesity and related metabolic diseases.